Digitalisasi Pendidikan Keuangan UMKM Dalam Meningkatkan Pengetahuan Keuangan Pengusaha UMKM Kota Tasikmalaya - Fauziyah, Azizah (Business Education Program of Universitas Pendidikan Indonesia, 2022)
The importance of delivering financial education digitally has grown along with the digitization of society and the economy in Indonesia, especially since the Covid-19 pandemic began to hit. Digitalization of financial education allows public authorities to reach a wider audience and increase the impact of financial literacy programs on various parties, one of which is for MSME entrepreneurs. This study aims to apply digital financial education for MSME entrepreneurs in order to increase financial knowledge as part of financial literacy that can help keep MSMEs running (sustainable development). The research method used is a quantitative method with the research subject of MSME entrepreneurs in the City of Tasikmalaya. The financial education provided for MSME entrepreneurs consists of materials on the Use of Financial Services, Business Financial Management and Planning, Risks and Dependents, and Financial Landscapes which are delivered digitally through the delivery of materials and online assistance using the zoom application. The results showed that digitizing financial education was able to increase the financial knowledge of MSME entrepreneurs in Tasikmalaya.